Thyroid and Aging or the Aging Thyroid? An Evidence-Based Analysis of the Literature - Aggarwal, Naveen (Hindawi Publishing Corporation, 2013)
Thyroid hormone production, metabolism, and action change with aging. The reference ranges for serum thyrotropin and thyroid hormones are derived mainly from younger populations. Thus, the prevalence of subclinical thyroid dysfunction is increased greatly in the elderly. However, it is unclear whether mild thyroid dysfunction in the elderly is associated with adverse outcomes. In this review, we discuss current evidence-based literature on thyroid function in the elderly and whether subclinical thyroid dysfunction in the elderly should be treated.